Affinity, Speciation, and Molecular Features of Copper(II) Complexes with a Prion Tetraoctarepeat Domain in Aqueous Solution: Insights into Old and New Results. Issue 11 (25th January 2013) - Di Natale, Giuseppe; Ősz, Katalin; Kállay, Csilla; Pappalardo, Giuseppe; Sanna, Daniele; Impellizzeri, Giuseppe; Sóvágó, Imre; Rizzarelli, Enrico
Abstract Characterization of the copper(II) complexes formed with the tetraoctarepeat peptide at low and high metal‐to‐ligand ratios and in a large pH range, would provide a breakthrough in the interpretation of biological relevance of the different metal complexes of copper(II)‐tetraoctarepeat system. In the present work, the potentiometric, UV/Vis, circular dichroism (CD), and electron paramagnetic resonance (EPR) studies were carried out on copper(II) complexes with a PEG‐ylated derivative of the tetraoctarepeats peptide sequence (Ac‐PEG27‐(PHGGGWGQ)4‐NH2) and the peptide Ac‐(PHGGGWGQ)2‐NH2. Conjugation of tetraoctarepeat peptide sequence with polyethyleneglycol improved the solubility of the copper(II) complexes. The results enable a straightforward explanation of the conflicting results originated from the underestimation of all metal–ligand equilibria and the ensuing speciation. A complete and reliable speciation is therefore obtained with the released affinity and binding details of the main complexes species formed in aqueous solution. The results contribute to clarify the discrepancies of several studies in which the authors ascribe the redox activity of copper(II)‐tetraoctarepeat system considering only the average effects of several coexisting species with very different stoichiometries and binding modes.